2016
DOI: 10.1186/s13073-016-0359-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics

Abstract: BackgroundSmith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors.MethodsWe investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 91 publications
(107 reference statements)
4
31
0
Order By: Relevance
“…For patients with molecular findings where photographs were available, images can be found in Supplemental Figure 1. This cohort of SMS-like individuals expands the published cohort of these individuals studied by exome analysis by 40% and identifies several genes that integrate into the proposed RAI1 -associated disease network (Loviglio et al 2016). …”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…For patients with molecular findings where photographs were available, images can be found in Supplemental Figure 1. This cohort of SMS-like individuals expands the published cohort of these individuals studied by exome analysis by 40% and identifies several genes that integrate into the proposed RAI1 -associated disease network (Loviglio et al 2016). …”
Section: Introductionmentioning
confidence: 76%
“…We explored if the genes harboring de novo variants were functionally associated with the network of genes recently identified in a separate SMS-like cohort (Loviglio et al 2016). This previous study identified variants in KMT2D (mapped to MLL2 by STRING), ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C , and POGZ .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations